PILAR PENDIDIKAN DALAM PERSPEKTIF IMAM AL-SYATHIBY - Samsuir, Al Ikhlas; Rivauzi, Ahmad; Wirdati, Wirdati (TARBAWY : Indonesian Journal of Islamic Education, 2018)
This study aims to reveal about the pillars of education in the perspective of Imam al-Syathiby. This research is library research where the authors explore the opinion of Imam al-Syathiby in the book al-Muwafaqat fi Ushul al-Syari’ah that related with education. After the data is collected, it is processed by qualitative approach method. The instrument in this study is the author himself. From this study it can be concluded that the concept of education according to Imam al-Syathiby has four pillars; first, materials (science), second, teacher, third, method and forth, student. Every pillar in education must be paid attention proportionally. If not, education will not work properly. The further impact is that the goodness of human life both in the world and in the hereafter will not be realized. In this world human will be miserable, in the hereafter they will be misfortune.Penelitian ini bertujuan untuk mengungkap tentang pilar pendidikan dalam perspektif Imam al-Syathiby. Penelitan ini berbentuk library research dimana penulis mengeksplorasi pendapat Imam al-Syathiby dalam kitab al-Muwafaqat fi Ushuli al-Syari`ah yang berkaitan dengan pendidikan.Setelah data terkumpul, diolah dengan metode pendekatan kualitatif. Adapun instrument dalam penelitian ini adalah penulis sendiri. Dari penelitian ini dapat disimpulkan bahwa konsep pendidikan menurut Imam al-Syathiby memiliki empat pilar, yaitu, materi (ilmu), guru, metode dan murid. Setiap pilar dalam pendidikan tersebut harus mendapatkan perhatian sesuai dengan porsinya. Jika tidak, maka pendidikan tidak akan berjalan dengan baik. Dampak lebih jauhnya adalah tidak akan terwujudnya kemashlahatan pada kehidupan manusia di dunia dan akhirat. Di dunia manusia akan sengsara di akhirat nanti manusia akan celaka.